FOREST ENGINEERING STUDENTS COMPETENCE DEVELOPMENT IN ADULT EDUCATION - Ruba, Jelena; Brizga, Dace; Svika, Diana; Miezīte, Olga; Sisenis, Linards (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Forest engineering students need to develop their competence in order to ensure a sustainable working environment in the relevant sector of economy. The aim of the study was to clarify the dynamics of the development of the students’ competence in the learning process. The methodological basis of the study included the analyses of the relevant publications in the context of competence and adult education. The authors’ personal reflections and work experience at the Forest Faculty of Latvia University of Life Sciences and Technologieswere taken into consideration. To assess the development of students’ competence in the forest engineering studies a survey was carried out. Within the framework of the study and as the result of improved adult studies, there was a significant improvement of students` competence in the field of forest engineering. The self-assessment of competence at the end of the course was higher than at the beginning of it.